Metal Metabolism in Aquatic Environments 1998
DOI: 10.1007/978-1-4757-2761-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of heavy metal accumulation and toxicity in fish

Abstract: INTRODUCTIONAs a result of mining, forestry, waste disposal and fuel combustion, our environment is becoming increasingly contaminated with heavy metals. The aquatic environment receives waste products from such activities and may be the final depository for these anthropogenic ally remobilized heavy metals. In order to understand the impact of heavy metals on aquatic biota it is important to characterize the mechanisms available for aquatic life to transport, immobilize and excrete heavy metals.Relatively lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 163 publications
3
90
0
Order By: Relevance
“…The results of this study showed that the highest heavy metal concentrations were found in the gills and livers of both sampled fishes. These results are similar to other studies that showed the bioaccumulation of heavy metals in the gills and livers of fishes was higher than the concentrations of heavy metals in the muscles of fishes [16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that the highest heavy metal concentrations were found in the gills and livers of both sampled fishes. These results are similar to other studies that showed the bioaccumulation of heavy metals in the gills and livers of fishes was higher than the concentrations of heavy metals in the muscles of fishes [16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…According to Alvarado et al (2005), lysosomal metal sequestering is considered a general strategy for reducing metal toxicity. Then, methyl mercury deposits in the cytoplasm of liver and kidney cells of C. carpio corroborate data of others authors (Olsson et al, 1998;Baatrup & Danscher 1987). …”
Section: Discussionsupporting
confidence: 90%
“…Trace elements accumulation in fish is dependent on numerous factors, and the accumulation pattern is the result of physiological uptake and elimination rates (Guven et al, 1999). Absorption of these elements may occur directly from the water, through the gills, but the main route seems to be the gastrointestinal absorption of those elements present in food (Olsson et al, 1998). Furthermore, because these species are apex predators, they carry out very intense metabolic activities that require a continuous supply of energy (Kojadinovic et al, 2007).…”
Section: A R T I C L E I N F Omentioning
confidence: 99%